Le indagini archeologiche di Cesare Colafemmina: le catacombe di Venosa nel carteggio con la Soprintendenza (1972-1980) - Mascolo, Mariapina (Sefer yuḥasin ספר יוחסין | Review for the History of the Jews in South Italy | Rivista per la storia degli ebrei nell’Italia meridionale, 2013)
In questo studio si presenta la corrispondenza intercorsa fra C. Colafemmina, il più importante studioso moderno delle catacombe di Venosa, e la Soprintendenza per i Beni Archeologici della Basilicata. Dalla documentazione emerge la cronologia esatta dei suoi studi sul sito e delle sue scoperte, nonché le circostanze entro cui ebbero luogo. Cesare Colafemmina’s Archaeological Investigations: The Catacombs of Venosa and His Correspondence with the Superintendency for the Archaeological Heritage (1972-1980) Cesare Colafemmina’s scientific production is marked by profound eclecticism, and in an interdisciplinary way, his research followed more than one direction: biblical exegesis, archaeology, history, art, literature and documents. Among his most important works there are those concerning the catacombs of Venosa, in Basilicata, to which he dedicated a ten year archaeological survey in the 70s and 80s. In his printed essays, Colafemmina often referred to survey campaigns, inspections and to excavation attempts, without, however, particularly dwelling upon these research stages, which are also very important for the correct reconstruction of the events regarding the catacombs and the history of their discovery. The article presents a study of the exchange of letters between Colafemmina and, in particular, the Soprintendenza per i Beni Archeologici della Basilicata, from which one can infer both the exact chronology of his research and discoveries and the atmosphere and circumstances in which they took place.